Descriptive labor market outcomes of immigrant women across Europe - Alícia Adserà; Ana M. Ferrer; Virginia Herranz (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
We consider the job progression of immigrant women in five European countries: France, Italy, Spain, Sweden and the UK. We complement data from the European Labour Force Survey (2005-2015), with information about the skills contained in the jobs held by women, using data from the O*Net. In particular, we focus on analytical and strength skills in immigrant's jobs and compare them to those required by jobs held by similar native women. Even though immigrants experience upon arrival a gap in participation relative to the native born, they gradually increase participation during the first ten years spent in the country (approximately, 1% per year in Spain, Italy and the UK, and 2% and 4 % per year in France and Sweden respectively). Our results reveal significant differences across countries of origin as well as differences within countries over the period of analysis. Recent immigrant women show relatively large gaps in the analytical skill content of the jobs they held relative to native-born women across our host countries. Further, with the exception of immigrants to Spain, they also work jobs with higher requirements of strength than their native-born counterparts do. Although educated immigrants show a different pattern in most countries (included Spain). We find differences within countries over the period of analysis that may be consistent with the variation of incentives to move depending on the business cycle at arrival - particularly given the meager opportunities in many destination countries during aftermath of the recent great recession.
Keywords: 330; Migranten; Weibliche Arbeitskräfte; Qualifikation; Erwerbsverlauf; Vergleich; Bevölkerung; EU-Staaten; Frankreich; Italien; Spanien